2010
DOI: 10.1016/j.pain.2010.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Mildly negative social encounters reduce physical pain sensitivity

Abstract: While previous research has demonstrated a reduction in physical pain sensitivity in response to social exclusion, the manipulations employed have arguably been far removed from typical daily experience. The purpose of this study was to investigate the effects of relatively ordinary social encounters on the perception of pain. Healthy participants rated the intensity and unpleasantness of painful stimuli before and after engaging in a structured interaction with a confederate who was instructed to either be wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 39 publications
2
24
0
Order By: Relevance
“…The results of this study are consistent with the notion that even food poverty and inquality can be stressful, in turn provoking a physiological reaction akin to that which occurs upon perception of a physical threat [42] one component of which can be hypoalgesia. Anatomical, pharmacological and behavioral evidence from stressed-induced analgesia studies revealed that amygdale, periaqueductal grey (PAG) and rostral ventromedial medulla (RVM) as critical structures, contribute to descending inhibitory pain pathways and lesions of these structures attenuate the conditioned stressed-induced analgesia response which can be mediated by opioid receptors [38], [42]. Opioids hypoalgesic effects are particularly prominent in inflammatory conditions [43].…”
Section: Discussionsupporting
confidence: 88%
“…The results of this study are consistent with the notion that even food poverty and inquality can be stressful, in turn provoking a physiological reaction akin to that which occurs upon perception of a physical threat [42] one component of which can be hypoalgesia. Anatomical, pharmacological and behavioral evidence from stressed-induced analgesia studies revealed that amygdale, periaqueductal grey (PAG) and rostral ventromedial medulla (RVM) as critical structures, contribute to descending inhibitory pain pathways and lesions of these structures attenuate the conditioned stressed-induced analgesia response which can be mediated by opioid receptors [38], [42]. Opioids hypoalgesic effects are particularly prominent in inflammatory conditions [43].…”
Section: Discussionsupporting
confidence: 88%
“…Two studies employed a social partner who interacted with the participant before but was absent during pain induction (Platow et al, 2007; Borsook and MacDonald, 2010). The first investigated whether the effects of reassuring comments depended on in-group or out-group status of the social partner, while Borsook and MacDonald studied socially induced hypoalgesia (reduced pain in the face of a stimulus that is normally perceived as painful; IASP, 1994) by negative vs. positive interpersonal interactions.…”
Section: Results and Their Organizationmentioning
confidence: 99%
“…However, reassurance from an in-group member did selectively reduce physiological arousal (Platow et al, 2007). Furthermore, negative interpersonal interactions preceding pain induction were associated with reductions in pain ratings, attributed to social harm induced hypoalgesia (Borsook and MacDonald, 2010). …”
Section: Results and Their Organizationmentioning
confidence: 99%
“…They found that when people believed that they would end up alone later in life, their pain threshold and tolerance significantly increased compared to non-rejected people. These findings have since been replicated (Borsook and MacDonald, 2010; Bernstein and Claypool, 2012). This suggests that social pain can cause people to become numb to physical pain, which is likely due to their shared neural substrates.…”
Section: Overlap Of Physical and Social Painmentioning
confidence: 79%